The approach of analytical psychology to child-mother relationship during the first year of life - Jusiene, Roma (Psichologija, 1995)
The paper analyses three different approaches to infant’s subjective life. They are: the psychoanalytical theory, the theory of analytical psychology and the theory of Self psychology about development in infancy, the infant-mother relationship and the formation of personality structure. The method of infant observation as one of the best ways to investigate the infant’s subjective experiences and infant-mother relationship is presented here. The significance of the method of infant observation to the theory and practise of analytical psychology and psychoanalysis is revealed. The possibilities of applying the method of infant observation in Lithuania are discussed.